Quadriceps Dysfunction Following Lung and Heart-lung Transplant: Magnitude, Nature, Contributing Factors and Clinical Implications - Watson, Carol (Curtin University, 2018)
This cross-sectional observational study explores the strength and endurance of the quadriceps femoris muscle in bilateral lung and heart-lung transplant recipients. Associations were sought between quadriceps femoris strength and endurance with functional measures of exercise capacity, sedentary time and time spent undertaking physical activity of different intensities. The study provides recommendations for exercise training strategies that may be used to enhance outcomes for transplant recipients.